2021
DOI: 10.1371/journal.ppat.1010036
|View full text |Cite
|
Sign up to set email alerts
|

Targeted transcriptomics reveals signatures of large-scale independent origins and concerted regulation of effector genes in Radopholus similis

Abstract: The burrowing nematode, Radopholus similis, is an economically important plant-parasitic nematode that inflicts damage and yield loss to a wide range of crops. This migratory endoparasite is widely distributed in warmer regions and causes extensive destruction to the root systems of important food crops (e.g., citrus, banana). Despite the economic importance of this nematode, little is known about the repertoire of effectors owned by this species. Here we combined spatially and temporally resolved next-generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Therefore, the lowest expression bin enriched in either -but in most cases both -effector-annotated genes and genes encoding putatively secreted proteins was used to define a cutoff for gland cell expression in each library. Above this cutoff, gland-expressed genes encoding putatively secreted proteins were considered putative effectors (Vieira et al 2021(Vieira et al , 2020Espada et al 2018). A majority (64%) of previously effector-annotated genes were recaptured above expression thresholds in gland cell libraries using this approach.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the lowest expression bin enriched in either -but in most cases both -effector-annotated genes and genes encoding putatively secreted proteins was used to define a cutoff for gland cell expression in each library. Above this cutoff, gland-expressed genes encoding putatively secreted proteins were considered putative effectors (Vieira et al 2021(Vieira et al , 2020Espada et al 2018). A majority (64%) of previously effector-annotated genes were recaptured above expression thresholds in gland cell libraries using this approach.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have identified 96 transcripts encoding for ShK domain-containing proteins from one of the most damaging PPN, B. xylophilus [9,33], and showed that the putative secreted proteins were enriched in these sequences-64% of these sequences encode a predicted signal peptide-which indicates that it might belong to secretory pathways. These proteins have also been found in the secretome of several animal parasitic nematodes (e.g., Teladorsagia circumcincta) [36] and other plant-parasitic nematodes, including B. xylophilus, P. penetrans, R. similis, and M. javanica [23][24][25]37]. The number of predicted ShK sequences constitutes one of the largest known protein families in Nematoda (e.g., T. circumcincta) [16,36], which is also observed in our data from B. xylophilus.…”
Section: Discussionmentioning
confidence: 99%
“…The nervous system is composed of major dorsal and ventral nerves along the body of the nematode, nearly associated with the epidermis, containing cell bodies that make and receive synapses with other neurons [39]. Some parasitic-related genes have been localized in nervous system tissues (e.g., R. similis) [23]. Curiously, a PWN catalase, which was used as a positive control for our ROS experiment, expressed in a transgenic C. elegans (for B. xylophilus catalase, Bxy-ctl-2, and BXY_1745800), was also localized in the nervous system [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations